STEGANALYSIS OF GRAPHIC CONTAINER - Shmatok, A. S.; Petrenko, A. B.; Yelizarov, A. B.; Tytov, V. A.; Borysenko, E. A. (Science-based technologies, 2013)
The author was motivated and on task elaboration algorithm of the software will perform a passive attack on the container of the amended by GSZ (Least Significant Bit) hidden information. The aim of the task was to automate the process of passive stegoanalysis graphics container with the help of statistical pattern recognition theory. This is achieved by aligning the statistical characteristics of the subject container and comparing it to the original container. The result of this comparison is the value which will include a container into two classes using this algorithm allows stegoanalitik check only suspicious containers, which significantly reduces the time spent compared to screen all containers and due to the continuing increase in the productivity of automated systems, time processing blocks automation algorithm stegoanalysis will decrease.